Intrinsic factors, adrenal gland morphology, and disease burden in captive cheetahs (Acinonyx jubatus) in South Africa. Issue 1 (27th December 2016) - Gillis‐Germitsch, Nina; Vybiral, Pamela‐Rose; Codron, Daryl; Clauss, Marcus; Kotze, Antoinette; Mitchell, Emily P.
Abstract : Adrenal gland weight (AW) and corticomedullary ratio (ACMR) are used as indicators of stress in animals. Captive cheetahs ( Acinonyx jubatus ) have higher ACMRs than free‐ranging ones and stress has been linked to gastritis, amyloidosis, glomerulosclerosis, and myocardial fibrosis. We reviewed age, sex, body weight (BW), kidney weight (KW), and left AW and ACMR with necropsy findings in 51 South African captive cheetahs. Eleven common histopathologic lesions were counted for each animal as measure of its disease burden. Adrenal corticomedullary hyperplasia was significantly correlated with left AW and ACMR. Males had significantly higher AWs than females; other parameters showed no difference between the sexes. Disease burden, gastritis, and myocardial fibrosis were moderately correlated with adrenal morphology supporting prior evidence that gastritis and myocardial fibrosis are linked to stress. Glomerulosclerosis was not correlated with adrenal morphology and neither kidney nor liver amyloidosis contributed significantly to variation in AW or ACMR on multivariate analyses. Interstitial nephritis showed much stronger correlations with kidney and liver amyloidosis than gastritis. All three adrenal parameters were correlated with age; age was the only significant variable affecting ACMR on the multivariate analyses; and disease burden as well as systemic amyloidosis and kidney disease (except for fibrosis) showed moderate correlations with age. Age may, therefore, be important in the pathogenesis of disease in captive cheetahs, particularly of amyloidosis and kidney disease. None of the intrinsic measurements or adrenal parameters were sufficiently closely linked to disease to be used as ante‐mortem proxies for disease burden or specific diseases. Zoo Biol. 36:40–49, 2017. © 2016 Wiley Periodicals, Inc.